Ptychography for Nonlinear Optical Microscopy - Norris, Evan (Université d'Ottawa / University of Ottawa, 2021)
In this thesis I will introduce a novel nonlinear optical microscopy method to address some of the shortcomings in the current nonlinear optical microscopy literature and offer a supplement to traditional fluorescent microscopy for label free optical biomedical imaging. In order to demonstrate this method I describe a method for the generation of a numerical sample of collagen fibrils, produce a set of numerical diffraction measurements. I introduce a novel Ptychography model for the simultaneous reconstruction of the components of the nonlinear optical susceptibility tensor and demonstrate the results of this model using numerically generated measurements from a numerical collagen sample. I additionally use the recovered information from Ptychography to retrieve new information about the structure of a sample.
Keywords: Nonlinear Optical Imaging; Ptychography